Two new species of fossil Corethrella Coquillett from Late Eocene Rovno amber, with a species‐level phylogeny for the family based on morphological traits (Diptera: Corethrellidae). (23rd February 2016) - BARANOV, VIKTOR A.; KVIFTE, GUNNAR M.; PERKOVSKY, EVGENY E.
Abstract: Species in the genus Corethrella Coquillett, the only genus in the family Corethrellidae, feed on the blood of frogs and toads and are unique among Diptera in locating their hosts by sound. Their fossil record goes back to the Cretaceous and comprises seven previously described species from various amber deposits. Herein, we present the first records of Corethrella from Late Eocene Rovno amber (35 Ma), with the description of two new species: Corethrella sontagae sp.n. based on a single male, and Corethrella rovnoensis sp.n. based on a single female. A revised key to fossil species of Corethrella is given. Phylogenetic relationships within Corethrella are investigated based on Bayesian and parsimony analysis, including the new data. All species groups recognized by Borkent (2008) are recovered as monophyletic, with the exception of the drakensbergensis group, which is found to be a paraphyletic grade. Both of the newly described species can be accommodated within modern species groups: C. sontagae shows affinities with the quadrivittata group and C. rovnoensis with the rotunda group. This published work has been registered in ZooBank, http://zoobank.org/urn:lsid:zoobank.org:pub:AE394C59‐775F‐42DC‐A5A8‐AF9C91E16464 .